Pengaruh Net Profit Margin (Npm), Return On Asset (Roa) Dan Return On Equity (Roe) Terhadap Harga Saham (Studi Kasus Pada Perusahaan Food And Beverage Yang Terdaftar Di Bei Tahun 2017-2019) - Sindi Ristanti; Ronny Malavia Mardani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThe aim of this study is to analyze the effect of net profit margins, asset returns and equity returns on food and beverage companies listed on the Indonesian Stock Exchange in 2017-2019. This study uses an explanatory study of the population of food and beverage companies listed on the Indonesian Stock Exchange in 2017-2019. The criteria used to determine the sample of the food and beverage company are the audited financial statements and the publication of their financial statements and the company was listed on the Indonesian Stock Exchange. With this method, a sample of 11 companies was obtained, The method of analysis used is the multiple linear regression modelThe findings of this analysis using a multiple linear regression method, which can be inferred the Net Profit Margin ( NPM) does not have a significant impact on stock prices, (2) Return On Assets ( ROA) does not have a significant effect on stock prices, and (3) Return On Equity ( ROE) has a significant effect on food and beverage company prices listed on the Indonesian Stock Exchange in 2017-2019. Keywords: Net Profit Margin (NPM), Return on Assets ( ROA), Return on Equity ( ROE) and Stock price.